Woman I Was Not Born To Be : a Transsexual Journey. - Brevard, Aleshia (Temple University Press, 2001)
Told with humor and flair, this is the autobiography of one transsexual's wild ride from boyhood as Alfred Brevard (""Buddy"") Crenshaw in rural Tennessee to voluptuous female entertainer in Hollywood. Aleshia Brevard, as she is now known, underwent transitional surgery in Los Angeles in 1962, one of the first such operations in the United States. (The famous sexual surgery pioneer Harry Benjamin himself broke the news to Brevard's parents.)Under the stage name Lee Shaw, Brevard worked as a drag queen at Finocchio's, a San Francisco club, doing Marilyn Monroe impersonations. (Like.